Kartoittava kirjallisuuskatsaus emulaatiopohjaisista ratkaisuista digitaalisessa pitkäaikaissäilytyksessä - Tynnyrinen, Mikko (2024)
In the past, emulation in digital preservation has been treated with reservations. Since then, the feasibility and realibility of emulation has been proven, but its use in digital preservation is still limited. This master's thesis aims to find out, through a scoping review, which strategies and tools have been developed to simplify the implementation of emulation, as well as how emulation has been applied complementary with other methods of digital preservation.